Experimental Study on Flow and Heat Transfer Characteristics of Jet Array Impingement Combined with Kagome Truss Structures with/without Cross-flow. (15th June 2023) - Ruan, Qicheng; Xu, Liang; Xi, Lei; Chen, Hanghang; Gao, Jianmin; Li, Yunlong
Highlights: Kagome truss structure of water-drop-shaped rods is proposed. Flow and heat transfer characteristics of the composite structures are conducted. The thermal performance of the new structure is better than the reference structure. The best thermal performances of the composite structures with cross-flow are found. Abstract: Jet array impingement providing high heat transfer are widely used in heat exchangers. However, the target plate is easily damaged impinged by high-speed air flow constantly. To solve this issue, Kagome truss structure is combined with jet array impingement to improve cooling performance in this paper. The flow and heat transfer characteristics of this composite structure in a heat exchanger unit with/without cross-flow were experimentally studied. Additionally, Kagome truss structures of circular and water-drop-shaped rods were used respectively in jet space and the results showed that the latter was beyond 7% higher than the former for the comprehensive thermal performance. When cross-flow was not added, the comprehensive thermal performance factor of the latter reached to a maximum of 1.656 at the Reynolds number of 5000. When cross-flow was added, the comprehensive thermal performance got worse at the cross-flow-to-jet velocity ratio of 1.0, while the best comprehensive thermal performances were found at the cross-flow-to-jet velocity ratio of 0.6 and at the mass flow rate proportion of cross-flow of 0.5, respectively. These results can provide a basic experimental data as a reference for designing new structures in advanced heat exchanger.